ANALISIS PERANAN TEKNOLOGI INFORMASI TERHADAP PERSAINGAN BISNIS ONLINE DI MASA PANDEMI COVID-19 - Farah Indah Azhari; Ifti Ayuni; Irham Lutfiansyah; Nurbaiti (Bajang Institute, 2022)
This study focuses on the use of information technology for business competition during the pandemic (covid-19). The purpose of this study is to analyze and use information technology to maintain business during a pandemic. The method used is a qualitative research method with a library research approach. The analytical method used is descriptive analysis, the data taken is secondary data, and the technique used is literature study. The results of the study show that: information technology is very influential on life, especially on business competition during the pandemic covid-19, During this pandemic the government is not allowed to leave the house so that people use information technology by shopping through e-commerce (online), The work of improving information technology today cannot be separated from the business world, because advances in information technology can provide different benefits and accommodations in conducting business exercises, the role of information technology in business is to gain or gain a comparative advantage. shows that information technology plays an important role in organizations by utilizing information technology, it is hoped that a company can explore its potential to the fullest and strive for excellence in the competition.